The American College of Radiology/Society of Breast Imaging Updated Fellowship Training Curriculum for Breast Imaging. Issue 4 (7th January 2021) - Katzen, Janine T; Grimm, Lars J; Brem, Rachel F
Abstract: Since the publication of the most recent breast imaging resident and fellowship curriculum in 2013, there have been widespread changes to the field of breast imaging. Screen-film mammography has been nearly completely replaced, and there has been widespread adoption of breast MRI and digital breast tomosynthesis. Fellowship training programs are increasingly one year in length, which accommodates the rapidly evolving subspecialized field of breast imaging. Recent surveys have identified deficits in nonclinical training related to patient communication and practice audits. This updated fellowship curriculum focuses on four discrete skill sets: clinical, noninterpretive, collaborative, and scholarly. Updates to the clinical curriculum include familiarity with new and emerging imaging technologies and biopsy techniques, as well as a more comprehensive understanding of breast pathology and appropriate follow-up and/or treatment recommendations. There is an increased focus on noninterpretive skills related to the practice audit and quality control. A formal communication curriculum tailored toward discussions with patients is highly recommended. The collaborative value of multidisciplinary care and the benefits of mentorship are emphasized. Finally, scholarly activities including both the opportunity for teaching and research, as well as dedicated lectures and journal clubs, will establish a platform for lifelong learning. This updated curriculum, which has been approved by the Executive Committee of the American College of Radiology and the Society of Breast Imaging Board of Directors, is designed to develop well-rounded fellowship graduates who are positioned to be breast imaging leaders within their future practices.